PENGABDIAN MASYARAKAT UNTUK MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN PARIWISATA BAGI MASYARAKAT DESA TARO KABUPATEN GIANYAR BALI - I Made Gede Darma Susila; Ni Luh Putu Sri Widhiastuty; L. K. Herindiyah Kartika Yuni; I Gusti Agung Bagus Widiantara; Ida Ayu Anggreni Suryaningsih (Universitas Triatma Mulya, 2023)
This training activity is a service program from the Faculty of Business and Tourism, Triatma Mulya University. In this activity, students are given the opportunity to enter the community and apply the knowledge they learn during lectures. Students will learn to overcome problems that occur in Taro Village and find solutions related to this. In addition, for lecturers, this activity is one form of implementation of the Tri Dharma of Higher Education carried out by community service. The purpose of dedication is to improve the competence of homestay owners regarding room division, and improve the knowledge and skills of tour guides in Taro Village. Service activities are carried out using the method of introduction, main activities and output activities. The findings in this service program are that Taro Village has human resources that are ready to serve tourists. Local community training activities are useful to increase knowledge and skills related to room division and tour guidance. In addition, the standard operating procedures prepared can guide the community in carrying out these competencies. Training the community in carrying out service activities to tourists is expected to be able to provide more experience so that it is better prepared to welcome the arrival of tourists who travel.